PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN TERHADAP KINERJA PELAYANAN ADMINISTRASI DI DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SUMBAWA - Abdul Rahim; S Syafruddin; Agus Alfisyahr (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the effect of management information system implementation on administrative service performance at the education and culture office of Sumbawa District. The type of this study was causal associative. The type of data used in this study was quantitative data obtained directly by the researcher from primary sources collected using a research instrument in the form of a questionnaire given to respondents. The respondents who were the source of data in this study were all employees at the Education and Culture Office of Sumbawa District, totaling 56 people. The data in this study was analyzed using statistical tests, including instrument quality tests, simple linear regression analysis, partial hypothesis tests, and coefficient of determination tests (R2). The results of this study showed that the implementation of management information system had a positive and significant effect on the performance of administrative services at the Education and Culture Office of Sumbawa District. The effect of management information system implementation on administrative service performance at the education and culture office of Sumbawa District was 64.6%, while the remaining of 35.4% was effected by other variables not examined in this study. The implementation of a management information system is very important in today's modern era, because through this system the development of information becomes more transparent and can be known by the general public, thus having an impact on improving the quality of education.